Gender bias in media representation of political actors: examples from Nigeria’s 2015 presidential election (2018)
As in other parts of the world, the Nigerian news media, in its coverage of electioneering, has been accused of marginalizing female politicians. To establish the veracity of this claim, we examined how Nigerian newspapers reported campaign activities of the major presidential candidates during Nigeria’s 2015 presidential election. Using the theories of media framing and market-oriented journalism, we undertook content analysis of 194 editions of three randomly selected newspapers—The Punch, The Guardian and the Daily Sun. The findings confirmed a media framing that marginalized female politicians as Nigerian newspapers gave prominence and intense coverage to male presidential aspirants as opposed to their female counterparts.